2001
DOI: 10.1002/1099-0690(200106)2001:11<2115::aid-ejoc2115>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions of Neutral 2-Azadienes with Enamines − Regiospecific Synthesis of Highly Substituted Dihydropyridines and Pyridines

Abstract: 2115ization of heterodienes gives pentasubstituted 2,3-dihydropyridines and pyridines in a regioselective fashion.this context, we have been involved in the synthesis of neutral [11] and electron-poor azadienes [9] as well as in the preparation of nitrogen-heterocyclic compounds. [5a,5c,14] As a continuation of our work on the [4ϩ2] cycloaddition chemistry of 2-azadienes, we aim here to explore a new and effective strategy for the preparation of pyridine derivatives through dimerization of electronically neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Subsequent oxidative aromatization furnishes the final product of a formal oxidative 1,3-shift of the sulfonyl group. [14] We carried out cross-over experiments to probe the intermolecularity of the sulfonyl 1,3-shift (Scheme 3 c). [15,16] When an equimolar mixture of 4 ae and 4 bf was heated at 130 8C under the catalytic conditions, the four expected products 3 ae, 3 af, 3 be, and 3 bf were detected by GC in a 1.1 : 1.4 : 1 : 1.1 ratio, which is consistent with our proposed mechanism.…”
Section: Dongqi Wang Fen Wang Guoyong Song and Xingwei Li*mentioning
confidence: 99%
“…Subsequent oxidative aromatization furnishes the final product of a formal oxidative 1,3-shift of the sulfonyl group. [14] We carried out cross-over experiments to probe the intermolecularity of the sulfonyl 1,3-shift (Scheme 3 c). [15,16] When an equimolar mixture of 4 ae and 4 bf was heated at 130 8C under the catalytic conditions, the four expected products 3 ae, 3 af, 3 be, and 3 bf were detected by GC in a 1.1 : 1.4 : 1 : 1.1 ratio, which is consistent with our proposed mechanism.…”
Section: Dongqi Wang Fen Wang Guoyong Song and Xingwei Li*mentioning
confidence: 99%
“…Furthermore, a pericyclic fashion was employed as an additional strategy to access these scaffolds. Palacios and co-workers have reported the synthesis of 1,2-dihydropyridines through a [4 + 2] cycloaddition reaction of 2-azadienes (readily prepared by aza-Wittig reactions) and enamines (Scheme b) . Tejedor et al has developed a convenient domino access to substituted alkyl 1,2-dihydropyridine-3-carboxylates from propargyl enol ethers and primary amines by means of a Claisen rearrangement/isomerization/amine condensation/6π-aza-electrocyclization process (Scheme c) .…”
mentioning
confidence: 99%
“…Palacios and co-workers have reported the synthesis of 1,2-dihydropyridines through a [4 + 2] cycloaddition reaction of 2-azadienes (readily prepared by aza-Wittig reactions) and enamines (Scheme 1b). 10 Tejedor et al has developed a convenient domino access to substituted alkyl 1,2dihydropyridine-3-carboxylates from propargyl enol ethers and primary amines by means of a Claisen rearrangement/ isomerization/amine condensation/6π-aza-electrocyclization process (Scheme 1c). 11 Very recently, Yu, Zhou et al reported the enantioselective synthesis of 1,2-dihydropyridines, using a chiral amine catalyst.…”
mentioning
confidence: 99%
“…However, 3,5-disubstituted pyridines have also been constructed through the multicomponent cyclization of small molecules. In 1953, Eliel and co-workers, while studying the synthesis of the alkaloid papaverine, were able to condense homoveratric aldehyde with ammonia. Instead of papaverine, they isolated a new compound characterized as 3,5-bis­(3,4-dimethoxyphenyl)­pyridine.…”
mentioning
confidence: 99%